3-tetrahydrofurfuryloxy-2-hydroxypropyl methacrylate: Synthesis, characterization, homo-polymerization, and copolymerization - Coşkun, Mehmet; Mürşit Temüz, M.; Ahmedov, Misir A. (Marcel Dekker Inc., 1996)
3-Tetrahydrofurfuryloxy-2-hydroxypropyl methacrylate monomer was prepared from methacrylic acid, tetrahydrofurfuryl alchol, and epichlorhydrin. Homopolymerization and copolymerization with (2-phenyl-1,3-dioxolane-4-yl)methyl methacrylate and N-vinyl pyrrolidone monomers were carried out in 1,4-dioxane solution at 60 °C using benzoyl peroxide as initiator. Infrared, proton and carbon-13 nuclear magnetic resonance techniques were used in characterizations of the monomer, the homopolymer and the copolymers were determined by DSC technique. The copolymer compositions were estimated from 1H-NMR spectra. The reactivity ratios in copolymerization of 3-tetrahydrofurfuryloxy-2-hydroxypropyl methacrylate and (2-phenyl-1,3-dioxolane-4-yl) methyl methacrylate were calculated by both Kelen-Tüdos and Fineman-Ross methods. Copyright © 1996 by Marcel Dekker, Inc.